Comparison of the Management of Digital TV via YouTube ‘RUBSARB Production Channel’ and ‘FEDFE Boyband Channel’ - ตระการบุญชัย, กัญฉกาจ (Siam Communication Review, 2017)
The purpose of this research paper “Comparison of the Management of Digital TV via YouTube ‘RUBSARB Production Channel’ and ‘FEDFE Boyband Channel’” was to study the management and production of the channel and how it has been promoted through the YouTube channel. This research paper has been done through the qualitative research by interviewing the management teams from both companies as well as other documentations provided by the companies and other media. We conclude that in order to produce successful channel on YouTube, that 1) Must have unique creativity with constant valuable contents 2) Must To produce a continuous video 3) also includes effective advertisement and promotion of clip in order to generate subscriber base 4) improve produce a quality channel to the viewers. 5) Must produce the information base on the facts and presented with sincerity.